1, 25(OH)2D3 improves blood lipid metabolism, liver function, and atherosclerosis by constraining the TGF-β/Smad signaling pathway in rats with hyperlipidemia. Issue 22 (17th November 2019) - Lu, Chunpeng; Yin, Yanping; Cui, Yongliang; Wang, Lili; Bai, Yan; Li, Jian; Huang, Tingting; Reziwanguli, Maimaiti; Miao, Lifu
ABSTRACT: 1, 25(OH)2 D3 has already been reported to function in some diseases. However, its role in hyperlipidemia (HLP) remains unknown. This study aims to investigate the effect of 1, 25(OH)2 D3 on HLP rats. Rat models were established by high-fat diet feeding, perfusion of different doses of 1, 25-(OH)2 D3 and injection of TGF-β1 siRNA. Whole blood viscosity, plasma viscosity, hematocrit, and erythrocyte aggregation index were detected, together with levels of biochemical indexes, 6-keto-PGF1α, and TXB2 in serum. Levels of oxidative stress indexes and inflammatory factors in serum and liver tissues were determined. TGF-β1 and Smad3 expression in serum, liver tissues, and aorta was detected. 1, 25(OH)2 D3 lowered HLP-induced rise of whole blood viscosity, red blood cell aggregation index, plasma viscosity, and hematocrit, TC, TG, LDL-C, apoB, ALT, AST, TXB2, MDA, IL-1β, TNF-α, and increased HLP-induced decrease of HDL-C, apoAI, 6-keto-PGF1α, SOD, GSH-Px, CAT, and T-AOC. TGF-β1 and Smad3 expression in serum, liver tissue, and aorta of 1, 25(OH)2 D3 -treated rats reduced. High 1, 25(OH)2 D3 dose and inhibited TGF-β/Smad signaling pathway alleviated lipid metabolism, liver function, and atherosclerotic injury in HLP rats. Our study found that 1, 25(OH)2 D3 improves blood lipid metabolism, liver function, and atherosclerosis injury by constraining the TGF-β/Smad signaling pathway in rats with HLP.